Two White Shirts. - ALI, KAZIM (American Poetry Review)
Every time I see two men in white shirts sitting next to each other, I think:This world needs me.I’m like a character in the old sci-fi shows.Not like Colonel Wilma Deering or Counselor Troi.I’m the alien princess from another planet with the crazy hair.I’m the bitch in the black dress who wants to kill you.